Speaking Performance of Islamic Boarding School and Public School-Based Graduates: A Comparative Study - Irfani, Bambang; Meisuri; Rohmatillah (JEELS (Journal of English Education and Linguistics Studies), 2018)
This study aims 1) to compare the speaking performance of university students who graduated from Islamic boarding school and public school-based senior high schools and 2) to investigate the potential factors affecting the difference of their speaking performance. First year students of a State Islamic University in Lampung - Indonesia participated as the subjects of research. The data of students’ speaking performance was obtained from the documentation of students’ speaking entrance test score. Then, a semi-closed-ended questionnaire investigating the curricular, co-curricular, and extra-curricular programs in their previous high schools covering the sorts, the frequency, and the duration of the activities was distributed to disclose the underlying reasons of the speaking performance differences. The results revealed that generally the Islamic boarding school-based senior high school graduates’ speaking performance is slightly better than the public-based one with a minor difference on the five aspects of speaking assessment. The former showed better achievement in fluency, vocabulary and comprehension, whereas the latter got better result in grammar and pronunciation. Dissimilar variations of the co-curricular and extra-curricular activities at both types of school and the frequency of the activities might be the potential factors affecting the differences.